Penerapan Algoritma K-Means Dalam Mengelompokkan Rata-Rata Konsumsi Kalori Menurut Provinsi - Sinaga, Juwitha Lovely Sweets; Solikhun, S; Suhendro, Dedi (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Calories are a source of energy that we get from food intake that contains nutrients and as a basic human need for humans to survive. The number of people who consume excessive calories and do not pay attention to the amount of calorie intake that is consumed will result in the emergence of various diseases that are bad for health. In this case the government does not have information about the data on the average calorie consumption per province by province. The purpose of this study is to determine the highest and lowest clusters, for that the authors use Data Mining with the K-Means Algorithm to classify Average Calorie Consumption per day by province. This test is carried out using RapidMiner software. The results were obtained from the average grouping of calorie consumption grouped by two clusters: high and low clusters, high clusters of 13 provinces and low clusters of 21 provinces. Provinces that are classified as low clusters are expected to be a contribution for the Indonesian government for decision making in an effort to maintain a balanced consumption of calories per day and create a healthy lifestyle program in the future.